Can Infant Dyschezia Be a Suspect of Rectosigmoid Redundancy? - Carmine Noviello; Stefano Nobile; Mercedes Romano; Letizia Trotta; Alfonso Papparella (MDPI AG, 2022)
Infant dyschezia is a functional gastrointestinal disorder that occurs in children less than nine months of age. This disorder causes much anxiety among parents who consult different physicians when suspecting major intestinal problems. The aim of this study is to verify whether infant dyschezia involves an anatomic abnormality (redundancy) of the colon. In this retrospective study (48 months) we analyzed all the children younger than 9 months who came to our attention through the suspicion of gastrointestinal abnormality (Hirschsprung's disease, anorectal malformations, colonic disorders or constipation). They all had a complete medical history, clinical examination and diagnostic tests, such as blood samples, suction rectal biopsy, a study of stool characteristics and, finally, a contrast enema. In cases with infant dyschezia, different colonic sizes and rectosigmoid length were measured, which created a ratio with the diameter of the second lumbar vertebra. These values were compared with those reported in the literature as normal for the age of one year. Of the 24 patients evaluated (mean age 4 months), 9 were excluded for different diagnoses (aganglionic megacolon, hypothyroidism, constipation). The comparison of the ratios obtained in the remaining 15 cases showed a significantly higher rectosigmoid length (redundancy) in children with dyschezia, 18.47 vs. 9.75 (p < 0.001). The rectosigmoid redundancy, a congenital anomaly already reported as a cause of refractory constipation, may be present in children with infant dyschezia.